WHY SERVICE DESIGN MATTERS: THE CASE OF NATIONAL LIBRARY OF LATVIA - Veliverronena, Linda; Grīnfelde, Ilze; Java, Oskars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
In the digital age when many organizations initiate and experience transformations as a reaction to wider societal changes, there is discussion about functionality, usability and availability of library services. Studies report a decreasing number of library visitors as result of the pervasive presence of the Internet as a faster source for getting resources, public`s lack of knowledge about the library services, etc. To maintain relevance for the public, more libraries apply principles of service design to provide an effective customer experience. For national libraries websites are of high importance as gateways to library resources and media to communicate institutions` objectives. The aim of this article is to analyse how the principles of service design are reflected in the online services offered by the National Library of Latvia. The research methods rely both on secondary data on audience needs and involve application of the service design principles to the website of National Library of Latvia. Results highlight the majority of analysed libraries apply the basic principles of service design and the focus is to provide the user friendly experience in libraries` databases and repositories. The website of the library provides limited user friendly experience in library`s and only partially follows the principles of service design.